THE ROAD TO GUEST DELIGHT: AN EMPIRICAL EXPLORATION IN THE HOTEL INDUSTRY - GOSWAMI, SINMOY (ASEAN Journal on Hospitality and Tourism, 2011)
Obtaining guest delight has been highly emphasized by every hotel in the present era of intense competition for securing guest loyalty. This study, therefore, aims to show how guest delight is formed in the hotels. It involved interviews of 500 repeat guests of 62 hotels in the 5 star deluxe, 4 star, 3 star, Heritage Grand and unclassified categories in India. Only guests on repeat visit to these hotels were included as sampling elements in this study as guest delight is applicable only to them. It was noticed that 46 variables including food and beverage quality, availability of food and beverage variety, hygiene of food and beverage etc. influence surpassing of guests’ expectations in these hotels. It is established in this study that surpassing of expectations of the guests affect their perception on pleasant surprises which, in turn affect their consequent happiness. Such happiness along with their perceived excitement and perceived positive feelings create a delighting experience for them.